The Jurisprudence of the Supreme Tribunal of the Lithuanian Republic in the Application of Local Customs in Peasantry Inheritance Cases - Machovenko, Jevgenij; Lytvynenko, Anatoliy (Teisė, 2023)
This article examines the cassational practice of the Supreme Tribunal of the Republic of Lithuania in peasant inheritance cases which were adjudicated in the 1920s and 1930s. The authors aim to describe the case law on the application of local customs as well as to determine whether the Supreme Tribunal of the Republic of Lithuania sought to expand, or, instead, to taper the scope of application of local customs in peasant inheritance disputes. The article paramountly utilizes the jurisprudence of the Supreme Tribunal of the Republic of Lithuania and the legal acts of the restored State of Lithuania, as well as the pre-war legal acts.